Simulated annealing algorithm for absolute value equations. (2017) - Moosaei, Hossein; Jafari, Hamed; Ketabchi, Saeed
The main goal of this paper is to compute the solution to the NP-hard absolute value equations (AVEs) Ax - |x| = b when the singular values of A exceed 1. First we show the AVE is equivalent to a bilinear programming problem and then we present a system tantamount to this problem. We use the simulated annealing (SA) algorithm to solve this system. Finally, several examples are given to illustrate the implementation and efficiency of the proposed method.